2022
DOI: 10.3390/su14063226
|View full text |Cite
|
Sign up to set email alerts
|

Application of Decoupling Approach to Evaluate Electricity Consumption, Agriculture, GDP, Crude Oil Production, and CO2 Emission Nexus in Support of Economic Instrument in Nigeria

Abstract: The paper appraised the nexus between electricity consumption, agriculture, GDP, oil production, and carbon dioxide (CO2) emissions in Nigeria using a decoupling approach. The result showed that agriculture, electricity, and GDP were predictive variables for CO2 emissions in the Granger causality analysis. The relationship between GDP and CO2 emissions also indicated that the amount of CO2 released tends to rise as the economy’s output and industrial sectors grow, making GDP and CO2 emissions increasingly rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Among the output indicators, the gross value of agricultural production is adjusted for the 2001-based producer price index for agricultural products in order to reduce the impact of price changes. Based on Liu et al [16], the accounting of agricultural carbon variables takes into consideration sources including cropland, tillage, livestock, fertilizers, pesticides, and mechanical power [17]. Reasons for choosing carbon emissions as a nondesired output are: this paper primarily centers on the impact of carbon emission changes on agricultural green total factors, in the context of achieving the dualcarbon target.…”
Section: Research Indicators and Data Sourcesmentioning
confidence: 99%
“…Among the output indicators, the gross value of agricultural production is adjusted for the 2001-based producer price index for agricultural products in order to reduce the impact of price changes. Based on Liu et al [16], the accounting of agricultural carbon variables takes into consideration sources including cropland, tillage, livestock, fertilizers, pesticides, and mechanical power [17]. Reasons for choosing carbon emissions as a nondesired output are: this paper primarily centers on the impact of carbon emission changes on agricultural green total factors, in the context of achieving the dualcarbon target.…”
Section: Research Indicators and Data Sourcesmentioning
confidence: 99%
“…The studies which discussed CO 2 emissions using the Johansen cointegration model were in different regions such as Asia [23,24], Africa [18,21,22], and Europe [17]. However, this was not the only tech-nique to understand how energy and economy affect the environment represented by CO 2 emissions, as some studies used the ARDL technique to reach their goals [15,19,20,27].…”
Section: Contextualization With Previous Researchmentioning
confidence: 99%
“…The authors of [55] stated a bidirectional causality between GDP growth and CO 2 e in the developing countries. Sane et al [56] analyzed how GDP and CO 2 e are more relevant to each other because of how economic growth will increase CO 2 e due to industrial sector expansion. Aslam et al [57] observed significant long-run relations between GDP and CO 2 e in Malaysia during 1971-2016 by using the ARDL method.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%